Development of an In Vitro Method to Estimate the Sensitization Induction Level of Contact Allergens. Issue 1 (21st February 2018) - Galbiati, Valentina; Gibbs, Sue; Roggen, Erwin; Corsini, Emanuela
Abstract: Recently, an in vitro procedure, which combines the epidermal equivalent potency assay with assessment of IL‐18 to provide a single test for identification and classification of skin sensitizers, was developed and validated. This unit will describe a simple in vitro method for estimation of the expected sensitization induction level interpolating in vitro EC50 and IL‐18 SI2 values to predict LLNA EC3 and/or human NOEL from standards curves generated using reference contact allergens, based on the use of Reconstituted human Epidermis (RhE).© 2018 by John Wiley & Sons, Inc.